2014
DOI: 10.1053/j.jvca.2014.05.010
|View full text |Cite
|
Sign up to set email alerts
|

Real-World Outcomes of Hemostatic Matrices in Cardiac Surgery

Abstract: These retrospective outcomes suggested FLOSEAL was associated with fewer negative consequences than SURGIFLO in this surgical population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
34
0
11

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(49 citation statements)
references
References 20 publications
4
34
0
11
Order By: Relevance
“…The most influential driver of cost, as detailed in the sensitivity analyses, was time spent in the OR performing surgery. This correlates with prior studies showing that FLOSEAL achieves hemostasis faster than SURGIFLO 3,4 . The strength of our analysis is derived from the Price et al 4 comparative effectiveness analysis of which it is based.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…The most influential driver of cost, as detailed in the sensitivity analyses, was time spent in the OR performing surgery. This correlates with prior studies showing that FLOSEAL achieves hemostasis faster than SURGIFLO 3,4 . The strength of our analysis is derived from the Price et al 4 comparative effectiveness analysis of which it is based.…”
Section: Discussionsupporting
confidence: 90%
“…Faivre et al 18 reported annual cost savings of e56,000-e344,000 with FLOSEAL use in MSS, and e40,000-e179,000 with FLOSEAL use in SSS in an economic analysis derived from Price et al 4 clinical inputs. Additionally, it is worth noting that our results are in agreement with a similar analysis of hemostatic matrix use in cardiac surgery 3 19 . This line of research has suggested that the differences between these flowable hemostatic agents results in different outcomes, some of which relate to patient safety, in both spine and cardiac procedures.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations